2020
DOI: 10.3390/jmmp4020058
|View full text |Cite
|
Sign up to set email alerts
|

3D Thermal Simulation of a Laser Drilling Process with Meshfree Methods

Abstract: Numerical simulation of laser drilling is rapidly gaining interest in academia and industry since this process remains one of the most important and widely-used technologies in modern manufacturing. Meshfree methods such as Smoothed Particle Hydrodynamics (SPH) have proven to be successful as a numerical tool for the computation of the heat transfer and material removal associated with a laser drilling problem. Nonetheless, the vast majority of recent developments incorporate an inconsistent SPH kernel into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Similarly, work by Romer et al [78] showed the finite difference time domain for modelling laser-produced nanostructures on a range of materials. Afrasiabi et al [79] showed the application of a particle strength exchange model that offers some advantages over more conventional FEM for modelling metal removal in laser drilling, and they later showed a mesh-free method for accurate three-dimensional thermal simulation during laser drilling [80].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, work by Romer et al [78] showed the finite difference time domain for modelling laser-produced nanostructures on a range of materials. Afrasiabi et al [79] showed the application of a particle strength exchange model that offers some advantages over more conventional FEM for modelling metal removal in laser drilling, and they later showed a mesh-free method for accurate three-dimensional thermal simulation during laser drilling [80].…”
Section: Introductionmentioning
confidence: 99%
“…Afrasiabi et al. [79] showed the application of a particle strength exchange model that offers some advantages over more conventional FEM for modelling metal removal in laser drilling, and they later showed a mesh‐free method for accurate three‐dimensional thermal simulation during laser drilling [80].…”
Section: Introductionmentioning
confidence: 99%
“…While relatively new in AM, the notion of SPH in modeling laser-based manufacturing processes is not entirely unique. Examples contain the use of SPH for modeling heat transfer in the laser ablation of aluminum (Alshaer et al , 2017) and an efficient thermal simulation of the laser drilling process with mesh-free schemes (Afrasiabi et al , 2018a, Afrasiabi and Wegener, 2020).…”
Section: Simulation Of Multimaterials Powder Bed Fusion Techniquesmentioning
confidence: 99%
“…The utilization of SPH in more industrially-oriented fields of application can also be found in the literature. Examples in laser-based manufacturing problems are the modeling of material removal in [8,9] and pulsed-laser ablation of aluminum in [10].…”
Section: Introductionmentioning
confidence: 99%